TINGKAT DISTORSI HARMONISA PADA LAMPU ESSENSIAL YANG BERBEDA MERK - Luqman Assaffat (MEDIA ELEKTRIKA, 2010)
Essential Lamp (SL) is a type of low pressure mercury lamp that worl<s leimlecittirnogn st hines icduer rtehnet tfuubnec atinodn .u Bsiencga uqsne e olefc trtohneic w sowriktcinhg e pqrLinipcmtpinlet , atsh ea ereispelanocsnei amthl eeln adtm isbpcah llcaasargtn ef o boerf classified as a non-linier electrical load It is callIend t hhea remleocntricics .p oHwaermr soynsitcesm ,a rae nmonu lltiinpel_easr olofathdesf rweiqll upernodcyu coe fa na feulnecdtarimcael iptaolwfreerq puoelnluctyio no.f wave. Harmonics generated by tlrc non-linier loads that - power system. So the harmonics will be able to disrupt thwe ipllo owrelur *qiutoatli"4 ta nodf edleelcivlreicreadl ptoow theer sysiems.As a non-linear load, essential lamps produce harmonic distortion, both harmonic currents and voltage- In this study concluded that the dffirent brands of essentiai lamp showed the dffirent value of Total HarmonicsDistortion (fHDKeyuords .Essensial Lamp, Harmonics, THD, power euality, pe Analyzer